Study of interleukin 8 (IL8) serum level in patients with chronic liver disease due to hepatitis C virus (HCV) with and without hepatocellular carcinoma (HCC) - Elewa, Hany; Abd-Elmeneem, Manal; Hashem, Ahmed Murad; Alshehaby, Aml (International Journal of Hepatology, 2010)
Background: HCC is a common complication of chronic hepatitis caused mainly by HCV. Interleukin-8 (IL8) is a cytokine involved in the cellular response to inflammation, being a powerful chemoattractant for neutrophils. Our objective was to estimate serum level of interleukin 8 in patients with chronic liver disease due to hepatitis C with and without hepatocellular carcinoma. Methods: This study included forty patients with chronic liver disease due to hepatitis C (twenty with and twenty without hepatocellular carcinoma) and ten control individuals. They were subjected to history taking, physical examination. liver function test and abdominal ultrasound. Serum level of interleukin 8 will be assayed by ELISA test for all patients. Serum alpha fetoprotien and CT abdomen were done according to each case. Results: From our study we found that serum IL-8 levels were higher in patients with HCV compared with control subjects, and in patients with HCC associated with HCV infection compared with control subjects. We found also that serum level of IL-8 is significantly higher in patients of chronic hepatitis C with HCC than patients of chronic hepatitis C without HCC. This study revealed also a positive significant correlation between size of tumor and IL-8 in HCC patients, while serum AFP level was not correlated to size of tumor. Serum level of IL-8 was found to be significantly correlated to platelet count and AST but not correlated to ALT in patients with HCC associated with HCV. Conclusions: From this study we conclude that serum IL-8 levels were higher in patients with HCV and patients with HCC associated with HCV infection compared with control subjects. Patients with HCC had higher serum IL-8 than patients with HCV without HCC. Serum interleukin 8 can be considered as a marker of HCC in patients with HCV related chronic liver disease. Key Words: Chronic Hepatitis C virus; Hepatocellular carcinoma; Interleuken 8 International Journal of Hepatology Vol.1(3) 2010 pp.9-17